2012
DOI: 10.1155/2012/475739
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and Severe Complications Are Worse for Octogenarians and Elderly Patients with Pelvis Fractures as Compared to Adults: Data from the National Trauma Data Bank

Abstract: Purpose. This study examined whether octogenarians and elderly patients with pelvic fractures have a different risk of complication and mortality as compared to adults. Methods. Data was gathered from the National Trauma Data Bank from 2002 to 2006. There were 32,660 patients 18–65, 6,408 patients 65–79, and 5,647 patients ≥ 80 years old with pelvic fractures. Descriptive statistics and bivariate and multivariate analyses were performed with the adult population as a referent. Results. Multivariate analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Others have shown that age, 13 the presence of shock on admission, and ISS score to be significant predictors of mortality which strongly supported our findings. 7 Interestingly, O'Brien et al found GCS, gender, and PF AIS to have no effect on mortality, results opposed to ours, which may be due to their smaller sample size (n = 305), the classification method of PF severity, and the inclusion of patients aged <65 years.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Others have shown that age, 13 the presence of shock on admission, and ISS score to be significant predictors of mortality which strongly supported our findings. 7 Interestingly, O'Brien et al found GCS, gender, and PF AIS to have no effect on mortality, results opposed to ours, which may be due to their smaller sample size (n = 305), the classification method of PF severity, and the inclusion of patients aged <65 years.…”
Section: Discussioncontrasting
confidence: 88%
“…12 Similar to our results, Matityahu et al reported older patients suffered more low energy falls rather than MVC. 7 However, a study performed by O'Brien et al found MVC followed by pedestrian struck to be more common in patients aged ≥55 years. 13 It is possible this is due to the study's smaller size (n = 57) or the inclusion of patients aged 55-64 years.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bone loss increases in women as they age result ing in widespread health problems, including chronic pain and fractures [21]. In addition, these risks contribute to shortened lifespan and reduced quality of life [22]. Increased cognizance regarding the health impacts of bone loss in later life, as well as the increasing frequency of such cases in ob/gyn practices, may mean that ob/gyns should pay closer attention to possible signs of bone loss in their patients.…”
Section: Bone Lossmentioning
confidence: 99%